Nitrate Pollution and Fecal Coliform Contamination in Domestic Wells in the Vavuniya District Sri Lanka with Special Reference to Hospital Area - Loganathan*, P. (Recent Research in Science and Technology, 2011)
Ground water is generallyÃ‚Â polluted by leachatesÃ‚Â from sewage andÃ‚Â agricultural lands. The main pollutants from sewages are nitrate nitrogen and fecal coliform. Both are hazardous when its level at high concentration in drinking water.Ã‚Â The objectives of the study were to evaluate the nitrate nitrogen and fecal coliform countÃ‚Â inÃ‚Â wells and identify the wells that are not suitable for drinking purpose in Vavuniya District, Sri Lanka.Ã‚Â Thirty threeÃ‚Â Ã‚Â dug wellsÃ‚Â and three tube wells were selected around the general hospital Vavuniya to measure the Nitrate Nitrogen (N03-N), and fecal coliform count from March 2008 to FebruaryÃ‚Â 2009. Mean NO3- N ranged from 0.40 to 16.2 mg/l over a twelve months period andÃ‚Â 30.5 % of the wells were above theÃ‚Â permissible limit of 10mg/l (well No11,12,13, 17,18,20,21,23, 25, 29Ã‚Â & 33) and theseÃ‚Â wells are not suitable for drinking purpose in almost all the months. Nitrate nitrogen in wet season was significantly higher than dry season (p= 0.072). The depth of wells varied from 4m to 8m and most ofÃ‚Â these wells were shallow wells. Shallow wellsÃ‚Â are very vulnerability to nitrate pollutionÃ‚Â in permeable soil. Almost all the wells were contaminatedÃ‚Â with fecal coliform.Ã‚Â Wells closer to sand bedsÃ‚Â were contaminated with very high amount (more than 500) ofÃ‚Â fecal coliform. ImproperÃ‚Â sewage disposal system could be the reason for high nitrate nitrogen andÃ‚Â fecal coliform contamination in wells around the hospital area.